PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK GADAI KONVENSIONAL DI PT.PEGADAIAN (PT.PEGADAIAN KANWIL I MEDAN) - Epinaldi Ginting; Ranto Nababan; Eva Sembiring; Deni Faizal Mirza (JURNAL ILMIAH SOCIO SECRETUM, 2021)
Quality of service and promotion is a very important role in business that is useful for advancing business and being able to help keep up with existing competitors. This research was conducted at PT. Pegadaian KANWIL 1 main branch of Medan. With the size of the sample taken was as many as 100 consumers. Test results simultaneously indicated Service Quality and Promotion had a positive effect on Purchasing Decisions at PT. Pegadaian KANWIL 1 main branch of Medan. With a calculated F value of 8.545 and a coefficient of determinant value of 0.194 or 19.4%. the results of the test partially showed that Service Quality had a positive effect on Purchasing Decisions at PT. Pegadaian KANWIL 1 main branch of Medan. Where the service quality variable had a t count of 4.255 and a t table value of 1.66039, with t count> t table (4.255> 1.66039) with a significant value of 0.000 <0.1. t count purchase decision was 2,572 and t table value was 1,66039, then t count> t table (2,572> 1,66039) with a significant value of 0.012 <0.1.